Fisiología Andina - Circulación - El rendimiento cardio-vascular al esfuerzo en el hombre de los Andes - Monge M., Carlos (1935)
In the previous communication we had necessarily refer to the performance of the heart against the effort to determine the frequency characteristics, shape, stability, etc., constituting man's pulse rate of the Andes. Indeed, we have noted the frequency of bradycardic and ortocárdicas reactions which are undoubtedly the best example of the physiological assessment of the Andean heart. So we said that the law of the Andean heart versus moderate or large effort, it is not a straight line as they occur at sea level - equal acceleration effort - but at the expense of the creek ortobradicárdicas reactions slowed to acceleration.